Aspek dalam Perancangan Fasilitas Duduk untuk Jalan Tunjungan, Surabaya: Gaya Desain Art Deco, Proxemics, Tempat Duduk sebagai Sarana Fasilitas di Tempat Umum, Aspek Pengguna, Aspek Fungsi, Aspek Sosial Budaya, Aspek Material, Aspek Rupa, Integrasi Aspek-Aspek Desain pada Perancangan Fasilitas Duduk - Wilson Takhta; Markus Hartono; Florentina Tiffany (Jurnal Desain Produk Nasional, 2024)
Tunjungan Street has become one of the historical public tourist destinations in the city of Surabaya. One of the attractions of Tunjungan Street is the architectural design of the buildings that still maintain their historical themes from the past. Art deco is a historical design style that is still preserved today on Tunjungan Street. However, the seating facilities along the Tunjungan Street area still have forms and functions that resemble the average seating facilities in various other public places. The purpose of researching aspects in the design of thematic seating facilities is to create an opportunity to beautify the tourist area and, at the same time, provide visual appeal for various activities conducted in the Tunjungan Street area. The method used in this research is the double diamond model, where the design process involves discovering and defining. Qualitative research is applied by collecting data through interviews with designers and psychologists, as well as observations of public tourist attractions. The collected data will be evaluated and used in designing a mind map. The innovative result of this research is the recommendation of aspects in the design of seating facilities for Tunjungan Street.